Sunday

April 19, 2015

April 19, 2015

Posted by **SAP** on Thursday, September 30, 2010 at 11:03pm.

16*(5/8 x+1/16 x) = 16(11/16+x)

10x + x = 11 + 16x, so the next step is:

11x = 11 + 16x (get x-terms on the left.)

-x = 11 (divide by -1.)

x = 11

Is this correct?

- math, really need some feedback asap. -
**TutorCat**, Friday, October 1, 2010 at 12:08amplug the value you found for x to determine whether or not this value is correct.

Like so:

5/8(11)+1/16(11)=11/16+ 11

11x = 11 + 16x

here's the next step:

11x-16x = 11

collect like terms and solve for x

- math, really need some feedback asap. -
**SAP**, Friday, October 1, 2010 at 12:27amhere's the next step:

11x-16x = 11 (collect like terms and solve for x.)

-5x = 11

-x = 11

x = 11

Thank you TutorCat, the answer does match.

- math, really need some feedback asap. -
**PsyDAG**, Friday, October 1, 2010 at 2:39pmPlease only post your questions once. Repeating posts will not get a quicker response. In addition, it wastes our time looking over reposts that have already been answered in another post. Thank you.

Again, dividing both sides by -5 does not give you

-x = 11

- math, really need some feedback asap. -
**SAP**, Friday, October 1, 2010 at 6:34pmYou are correct, 11/5 = 2.2. Do I need to round off for a single integer?

Math - 5(-3x - 2) - (x - 3) = -4(4x + 5) + 13 Answer Multiply factors. -15x - 10...

Algebra - There are two solutions to | 16x - 5 | = 3. The greatest solution is ...

algebra - Solve the system by addition or substitution. 16x-4y=20 y=4x-4 I ask ...

Pre-Calculus - Help please If f(x)=8x and g(x)=2x+1 find (fog)(x) 16x^2+8x 16x+1...

Math - algebraish - hey how do we convert y=mx+b to standard form? the standard ...

math need asap - 5/8 x+1/16 x=11/16+x 16*(5/8 x+1/16 x) = 16(11/16+x) 80 + x + ...

calculus - i need to find the derivative using chain rule: (x^2 + 2x - 6)^2 (1-x...

Intermediate Algebra - Am I going in the right track? 8x -1/x + 5x - 3/2x = 16x^...

Math - For Reiny:What step did I do wrong.(Help) (x-4x^3)^2 =(x-4x^3)(x-4x^3)=(x...

algebra - x^2 +16x+64 x^2+16x=64 (x=3)^2=16x-64 16x=-64 x=-4 Check this problem ...